PENGARUH TAX AWARENESS, TAX MORALE, DAN PEER GROUP TERHADAP TAX COMPLIANCE WAJIB PAJAK ORANG PRIBADI DENGAN INTENTION TO COMPLY SEBAGAI VARIABEL MEDIASI - Zahirah, Aishwarya Shafa; Dwi Suhartini (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This research aims to investigate the many variables influencing tax compliance among individual taxpayers at KPP Pratama Surabaya Rungkut. It will examine the importance of tax awareness, tax morale, and the impact of peer groups, emphasizing the desire to comply as a mediating variable. Methods: This study employed a quantitative methodology, gathering primary data through questionnaires distributed in both online and offline formats to a sample of 100 individual taxpayers registered at KPP Pratama Surabaya Rungkut. Data analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM).Results: The results show that being more conscious of taxes and having a strong sense of tax morality both make people more likely to comply, which in turn has a big effect on how well they really do. Simultaneously, peer groups seem to exert little influence on the desire to comply or on actual tax compliance. An in-depth analysis reveals that the desire to comply serves as a mediator in the relationship between tax knowledge and tax compliance (complete mediation) as well as in the relationship between tax morale and tax compliance (partial mediation). The results support the Theory of Planned Behavior, emphasizing that intention serves as a key predictor of actual behavior. This research suggests that enhancing internal motivation via tax education and the development of moral values may be an effective strategy to increase tax compliance among individual taxpayers in metropolitan areas like Surabaya. Keywords: Tax Awareness, Tax Morale, Peer Group, Intention to Comply, Tax Compliance